Structural Reforms and the Enlargement of Monetary Union - Carsten Hefeker (Center for Economic Studies and ifo Institute (CESifo), 2000)
The paper addresses the question what effects the enlargement of a monetary union will have on necessary structural refoms in the (low distortion) member countries and the (high distortion) candidate country. While monetary union lowers reforms in the candidate country, members of the monetary union will increase their reform efforts. The paper then proceeds to derive the conditions if and when the countries agree to an enlargement of the monetary union.
Keywords: 330; Monetary union; asymmetric shocks; inflation; structural reforms; convergence